Membrane-active and DNA binding related double-action antimycobacterial mechanism of antimicrobial peptide W3R6 and its synthetic analogs - Wang, Xiaorui; Feng, Liubin; Li, Mengmiao; Dong, Weibing; Luo, Xueyue; Shang, Dejing (Biochimica et biophysica acta. General subjects, 2023)
The emergence of multidrug- or extremely drug-resistant M. tuberculosis strains has made very few drugs available for current tuberculosis treatment. Antimicrobial peptides can be employed as a promising alternative strategy for TB treatment. Here, we designed and synthesized a series of peptide sequences based on the structure-activity relationships of natural sequences of antimicrobial peptides. The peptide W3R6 and its analogs were screened and found to have potent antimycobacterial activity against M. smegmatis, and no hemolytic activity against human erythrocytes. The evidence from the mechanism of action study indicated that W3R6 and its analogs can interact with the mycobacterial membrane in a lytic manner and form pores on the outer membrane of M. smegmatis. Significant colocalization of D-W3R6 with mycobacterial DNA was observed by confocal laser scanning microscopy and DNA retardation assays, which suggested that the antimycobacterial mechanism of action of the peptide was associated with the unprotected genomic DNA of M. smegmatis. In general, W3R6 and its analogs act on not only the mycobacterial membrane but also the genomic DNA in the cytoplasm, which makes it difficult for mycobacteria to generate resistance due to the peptides having two targets. In addition, the peptides can effectively eliminate M. smegmatis cells from infected macrophages. Our findings indicated that the antimicrobial peptide W3R6 could be a novel lead compound to overcome the threat from drug-resistant M. tuberculosis strains in the development of potent AMPs for TB therapeutic applications. •The analogs of W3R6 with lipophilic alkyl tails were screened with potent antimycobacterial activity against M. smegmatis•The secondary conformation of W3R6 was identified by NMR spectroscopy.•The analogs of W3R6 can interact with the mycobacterial membrane in a lytic manner.•The analogs of W3R6 can translocate the mycobacterial cell membrane and targeted to the genomic DNA of M. smegmatis.